2023
DOI: 10.1088/1402-4896/acb861
|View full text |Cite
|
Sign up to set email alerts
|

Synergetic role of Ni and GOns to improve the microstructure and mechanical creep rate of Sn-5.0Sb-0.7Cu solder alloy

Abstract: The role of minor additions of Ni and GOns to Sn- 5 wt.% Sb- 0.7 wt.% Cu (SSC-507) has been explored. Findings of scanning electron microscopy (SEM), energy dispersive X-ray spectrometry (EDX), and X-ray diffractometry (XRD) display the new phases like (Cu,Ni)6Sn5 and the size decrement of β-Sn grains. A slight increase in the melting temperature was observed using differential scanning calorimetry (DSC) analysis due to adding Ni (ΔTm =1.02 oC) and GOns (ΔTm =0.75 oC). Interestingly, 0.1 wt% Ni addition reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Consequently, the improvement in creep resistance was mostly due to the finer grain size of the β-Sn grains and the more uniform dispersion of the IMC particles. The same dependency was obtained by Mousa et al [33].…”
Section: Tensile Creep Deformationsupporting
confidence: 87%
See 3 more Smart Citations
“…Consequently, the improvement in creep resistance was mostly due to the finer grain size of the β-Sn grains and the more uniform dispersion of the IMC particles. The same dependency was obtained by Mousa et al [33].…”
Section: Tensile Creep Deformationsupporting
confidence: 87%
“…The thermal profiles obtained during heating lead-free SSC solder specimens doped with 2. These values are largish than that for SSC507 solder (7.1 °C) [33], Sn-0.7Cu-0.5Co solder (6.6 °C) [43], and close to 11.5 °C for Sn-Pb eutectic [44]. The observed reduction in the pasty range for 0.25, 0.75, and 1 wt% of Co additions has significant effects on both the performance and reliability of SSC-xCo solders in electronic service as they facilitate rapid soldering, decreased porosity, and the possibility of fillet lifting.…”
Section: Thermal Analysismentioning
confidence: 59%
See 2 more Smart Citations
“…Nickel's overall importance in soldering is growing, where Ni is utilized as a barrier to diffusion within Cu and Sn in order to avoid and slow the production of Cu 3 Sn and Cu 6 Sn 5 intermetallic phases during soldering or to extend the shelf life of printed circuit boards (PCBs) with solderable tin plated surface finishes [23][24][25]. Interfacial reactions between Sn-Zn solder and Ni were studied by Wang et al [26] They found that the Sn-9wt% Zn/Ni interfacial reactions are controlled by diffusion processes and that Ni 5 Zn 21 is the predominant produced phase for solid-state ageing between 150 °C and 170 °C and liquid-state ageing between 230 °C and 270 °C.…”
Section: Introductionmentioning
confidence: 99%